Adaptability in teaching and learning during COVID-19 / Haliza Ab Ghani, Nor Azah Mohd Rathi and Zaemah Abdul Kadir - Ab Ghani, Haliza; Mohd Rathi, Nor Azah; Abdul Kadir, Zaemah (UiTM Press, 2022)
The COVID-19 pandemic has impacted traditional learning from primary to tertiary levels. UiTM lecturers were forced to embrace online learning. Academics were asked to learn, create, and implement open and distance learning (ODL) using a variety of platforms, even if they did not feel adequately prepared or had previously expressed little interest in online teaching. The primary goals of the study were to investigate their readiness for online teaching as well as the challenges they faced. Two sets of survey questions were sent to all lecturers teaching in Akademi Pengajian Bahasa, Shah Alam. The findings show that participants not only adapted to online teaching but also learned new knowledge during the online teaching and learning. Participants also stated that the main issues they encountered were internet connectivity among students and lecturers. This indicates that internet connectivity plays a major challenge during ODL. It is hoped that this research will serve as a guide for Akademi Pengajian Bahasa management in assisting lecturers who are still struggling with ODL.